Cirrhosis aggravates the ninety-day mortality after liver resection for hepatocellular carcinoma - Abdelhameed, Hosam Farouk; El-Badry, Ashraf M. (International Surgery Journal, 2019)
Background: Ninety-day postoperative mortality (90-D POM) measures accurately the liver resection-related mortality. In cirrhotic patients, reporting post-hepatectomy-related death only as in-hospital or thirty-day postoperative mortality (30-D POM) may underestimate cirrhosis-related death after liver resection. Methods: Medical records of adult cirrhotic (cirrhosis group) and matched non-cirrhotic (control group) patients, who underwent elective liver resection at Sohag University Hospital (April 2014- March 2018), were analyzed. The 90-D POM versus in-hospital mortality and 30-D POM were compared in both groups. Results: Forty-six patients (23 per group) were eligible for the study. Liver resection was carried out in all cirrhosis group patients for hepatocellular carcinoma (HCC). In the control group, liver resection was indicated for colorectal metastasis (13), benign masses (7) and intrahepatic cholangiocarcinoma (3). Compared with the control group, cirrhotic patients exhibited significantly higher complication rates (p<0.05), prolonged hospital stays (p<0.05), increased postoperative levels of serum bilirubin and reduced prothrombin concentration (p<0.05). In the control group, in-hospital mortality and 30-D POM were zero while 90-D POM was 4%. In the cirrhosis group, the in-hospital mortality and 30-D POM were identical (8.7%), however the 90-D POM was significantly higher and almost doubled (17%). Conclusion: Liver cirrhosis triggers significant mortality that may extend for ninety days postoperatively. In cirrhotic patients, post-hepatectomy death should be reported as 90-D POM rather than the obviously misleading in-hospital mortality or 30-D POM.